2016
DOI: 10.1016/j.atherosclerosis.2016.01.036
|View full text |Cite|
|
Sign up to set email alerts
|

RVX-208, a BET-inhibitor for treating atherosclerotic cardiovascular disease, raises ApoA-I/HDL and represses pathways that contribute to cardiovascular disease

Abstract: High density lipoproteins (HDL), through activity of the main protein component apolipoprotein A-I (ApoA-I), can reduce the risk of cardiovascular disease (CVD) by removing excess cholesterol from atherosclerotic plaque. In this study, we demonstrate that the bromodomain and extraterminal domain (BET) inhibitor RVX-208 increases ApoA-I gene transcription and protein production in human and primate primary hepatocytes. Accordingly, RVX-208 also significantly increases levels of ApoA-I, HDL-associated cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 57 publications
(59 reference statements)
5
92
0
3
Order By: Relevance
“…This single target approach has the potential to impact multiple dysregulated genes and biological pathways that are known to drive vascular disease. Recent findings have demonstrated apabetalone treatment can reduce expression of calcification and vascular inflammation biomarkers, as well as factors both in the fibrin clotting cascade and the complement system [9, 10]. These pathways play a potential role in the biology underlying the pathogenesis of diabetes and CKD as well as cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This single target approach has the potential to impact multiple dysregulated genes and biological pathways that are known to drive vascular disease. Recent findings have demonstrated apabetalone treatment can reduce expression of calcification and vascular inflammation biomarkers, as well as factors both in the fibrin clotting cascade and the complement system [9, 10]. These pathways play a potential role in the biology underlying the pathogenesis of diabetes and CKD as well as cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pharmacokinetic study of apabetalone treatment in patients with late stage CKD revealed that a single dose of apabetalone rapidly downregulated multiple CKD and CVD protein markers, and associated molecular pathways [11]. Moreover, in the phase II clinical studies with apabetalone, patients treated with apabetalone were less likely to experience a major adverse cardiovascular event (MACE) and experienced reductions in CKD risk factors such as ALP [9]. ALP catalyzes the breakdown of inorganic pyrophosphate, which functions as an important inhibitor of calcification and mineralization [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It increases apolipoprotein AI (ApoA-I) gene transcription and leads to production of high density lipoprotein (HDL) cholesterol levels in vitro and in vivo , 157 resulting in the stimulation of reverse cholesterol transport. It also represses inflammatory and atherosclerotic pathways that contribute directly to cardiovascular risk 158 . RVX-208 is also being tested in patients with pre-diabetes, demonstrating effects in HDL lipidome and glucose metabolism that may protect against the development of type 2 diabetes 159 …”
Section: Targeting Protein Acetylation Beyond Bromodomain Inhibition mentioning
confidence: 99%
“…Gene expression was measured by TaqMan-based real-time PCR using the RNA UltraSense One-Step qRT-PCR System, as described previously (McLure et al, 2013;Gilham et al, 2016). mRNA levels were measured relative to an endogenous control on 7500 or ViiA-7 Real Time PCR Instruments (Applied Biosystems, Foster City, CA).…”
Section: Real-time Pcrmentioning
confidence: 99%